Measuring pest control services provided by biodiversity in multiple agricultural landscapes - Denan @ Adnan, Nuradilah (2020)
Non-selective pesticides have caused extensive loss to animal biodiversity in the agroecosystem. Moreover, the loss of tropical forests due to agricultural activities and overuse of pesticides in homogenous habitat affects overall biodiversity and ecosystem functions. To provide solution, biological control is alternatives to chemical pesticides. The main issues were how different types of agricultural landscape (oil palm, rubber tree plantation and fruit orchard) and the interior and edge effect of different ages of oil palm contributes to predation by natural enemies on pest insects. This research investigates the potential of birds, small mammals, and arthropods as natural enemies for pest insects in agricultural landscapes. The methodology was divided into two frameworks. First, a study was conducted in Pedas Negeri Sembilan to determine the predation rate within fruit orchards, oil palm, and rubber tree plantations using predation marks left on the artificial caterpillar. Local/site and landscape variables including understory vegetation structures, elevation, proximity to forest, and canopy cover from the three-agriculture landscape, were collected. The data were analyzed using Generalized Linear Mixed Models (GLMMs) with predation as the response variable. Binomial distribution was used and variables were fitted with plot as random effects. The effect between land-use type and predator type was significant. In all three land-use types, arthropods and mammals were important enemies of artificial caterpillars and there was little predation by birds. In fruit orchards and rubber tree plantations, mammal’s predation was considerably higher likely due to the landscape ability to support higher abundances of insectivorous mammals. The second framework was conducted in Universiti Putra Malaysia Serdang Selangor to determine the predation on artificial caterpillar using variables comprising height and coverage of understory vegetation, elevation and, canopy cover from the edge and interior location of three different oil palm age stand. The binary regression was used to analyzed the relationship between the variables and complemented with Nagelkerke R2 coefficient. The results revealed that mammals responsible for the highest levels of predation, followed by arthropods and birds. Arthropod predation was higher at edge locations, abandoned habitats, and elevated areas. Mammal predation was shown to increase with understory coverage and decrease with elevation. Bird predation was not shown to be associated with any of the habitat quality characteristics studied. Overall predation was higher at the edge of plantations and positively correlated to understory vegetation coverage regardless of plot location. Throughout the research, types of habitat and habitat quality such as understory vegetation and edge location have distinct effect on the natural enemy population. The diversity and abundance of arthropods and mammals should be maintained by tolerating understory vegetation and minimizing the application of pesticides. A practical approach, such as reserving a semi-natural habitat of different types of vegetation within agricultural land to restore suitable foraging and refuge habitat for natural enemies. Besides, through the implementation of biodiversity-friendly management, there is real potential to improve the effectiveness of natural enemies within agricultural landscapes. The findings promote sustainable agriculture at the landscape level and offer an opportunity to increase crop yields.